Pengaruh Kompetensi, Disiplin dan Lingkungan Kerja Terhadap Kualitas Pelayanan Pada Kantor Camat Denpasar Timur - Tri Indarwati (Public Inspiration : Jurnal Administrasi Publik, 2020)
One of the step to take by Kantor Camat Denpasar Timur in order to make growth up well quality of service are to pay attention or focus on the competency, discipline and work environment. which one by first observation find any problem are placement of employee not agree with their skill, employee infraction regulation, relationship between employee not harmonic and compline from customer about quality of service. The formulation of the problem in this research is whether competency has the influence to quality of service at Kantor Camat Denpasar Timur, whether discipline has the influence to quality of service at Kantor Camat Denpasar Timur, whether work environment has the influence to quality of service at Kantor Camat Denpasar Timur, whether competency, discipline and work environment has in simultaneous influence to quality of service at Kantor Camat Denpasar Timur. To solve the problems, the research used theory’s they are competency by Sanjaya (2006), discipline by Gorda (2004), work environment by Sedarmayanti (2013:131) and quality of service by Parasuraman (Tjiptono (2006:26), and also conducted quantitative method by questioner. Questioner to 31 people of sample, and then analysis technique used is linier regression analysis. Result of this research: Result of this research: competency has positive and significant influence to employee performance at quality of service at Kantor Camat Denpasar Timur because result in partial of the exam that coefficients regression of competency is 0,670 and coefficients t-test of competency is 2,4187 whit coefficients significant is 0,023. discipline has positive and significant influence to quality of service at Kantor Camat Denpasar Timur. Work environment has positive and significant influence to quality of service at Kantor Camat Denpasar Timur, because result in partial of the exam that coefficients regression of discipline is 3,043 and coefficients t-test of discipline is 5,481 whit coefficients significant is 0,000. Work environment has positive and significant influence to quality of service at Kantor Camat Denpasar Timur, work environment has positive and significant influence to quality of service at Kantor Camat Denpasar Timur, because result in partial of the exam that coefficients regression of work environment is 0,357 and coefficients t-test of work environment is 2,300 whit coefficients significant is 0,029. Competency, discipline and work environment has positive and significant in simultaneous influence to employee performance at quality of service at Kantor Camat Denpasar Timur, because result of analysis that coefficients determinant 92,4% and coefficients F-test 109,955 whit coefficients significant is 0,000.